2009
DOI: 10.1002/app.31489
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chemical compositions on the properties of random and multiblock sulfonated poly(arylene ether sulfone)‐based proton‐exchange membranes

Abstract: The influence of chemical compositions on the properties of sulfonated poly(arylene ether sulfone)based proton-exchange membranes was studied. First, we synthesized three different series of random SPAES copolymers using three kinds of hydrophobic monomers, including 4,4 0 -dihydroxyldiphenylether, 2,6-dihydroxynaphthalene (DHN), and 4,4 0 -hexafluoroisopropylidenediphenol (6F-BPA) to investigate effects of hydrophobic components on the properties of SPAES membranes as proton-exchange membranes. Random SPAES c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 89 publications
2
8
0
Order By: Relevance
“…Research findings also showed that sulfonated PAEs containing -CF 3 moieties in the polymer backbone had higher proton conductivity compared with their non-fluorinated analogues [95]. Fluorinated PAEs have better phase-separated morphology and good proton conductivity.…”
Section: Scheme 225 Structure Of Copolymers Prepared From Polycondenmentioning
confidence: 92%
“…Research findings also showed that sulfonated PAEs containing -CF 3 moieties in the polymer backbone had higher proton conductivity compared with their non-fluorinated analogues [95]. Fluorinated PAEs have better phase-separated morphology and good proton conductivity.…”
Section: Scheme 225 Structure Of Copolymers Prepared From Polycondenmentioning
confidence: 92%
“…[6] A great interest is currently focused on microphase separated block copolymers with highly sulfonated blocks to improve the proton conductivity at high temperatures and low relative humidity. [7][8][9][10][11][12][13] Two multiblock copoly(arylene ether sulfone)s with similar block lengths and ion exchange capacities (IECs) were prepared by a coupling reaction between a non-sulfonated precursor block and a highly sulfonated precursor block containing either fully disulfonated diarylsulfone or fully tetrasulfonated tetraaryldisulfone segments. The latter two precursor blocks were sulfonated via lithiation-sulfination reactions whereby the sulfonic acid groups were exclusively placed in ortho positions to the many sulfone bridges, giving these blocks IECs of 4. , prepared by using SDCDPS and hydroquinone.…”
Section: Introductionmentioning
confidence: 99%
“…To solve these problems, efforts have been made to develop alternative PEMs. One solution is to develop novel alternative PEMs based on the sulfonated aromatic hydrocarbon polymers, such as sulfonated poly(arylene ether sulfone)s, sulfonated poly(arylene ether ketone)s, sulfonated polyimides, and sulfonated organic–inorganic hybrids . The other is to modify Nafion membrane, including the reinforcement of Nafion membrane with a supporting porous substrate, the incorporation of inorganic fillers and the forming of methanol‐blocking layer …”
Section: Introductionmentioning
confidence: 99%